Educational Quality Assurance and National Educational Standards - Phumphongkhochasorn, Phumphakhawat (Asia Pacific Journal of Religions and Cultures, 2021)
Nowadays, it is widely accepted that quality and educational standards are important for all parties involved. In the provision of education must be aware and proceed to achieve results in accordance with the educational standards set. The educational quality assurance system is an important mechanism to help improve the quality and education standards effectively. National Education Act 1999 and as amended to (No. 3) 2010 Sort 6 Section 48 specify that the jurisdiction and the educational institution have established the internal quality assurance system of the school and consider the internal quality assurance as part of the educational administration process that must be continuously implemented. School prepares an annual report for submission to related departments in order to improve the quality according to educational standards and support external quality assessments afterward. Ministry of Interior has announced early childhood education standards, Basic education standards and practice guidelines for educational quality assurance for internal quality assurance of schools under the local administrative organization. They set standards and issues for consideration to be less, more compact, truly reflect quality, emphasize on real assessment, not complicated, create standardized assessment system, reduce the storage burden, and reduce the preparation of documents used for evaluations. The guidelines for evaluating the quality of the schools will focus on the collection of qualitative data in accordance with the school's context. They do not increase the burden of document preparation for schools and develop internal assessors to have standards, to be reliable, able to give advice and give advice to educational institutions, to adjust the evaluation paradigm that aims to develop based on the context of the school and the educational standards of the school, to determine and share responsibility for the results of the educational management Education is processes that gives people the knowledge and qualifications and help that person survive in the world to benefit him, family and society as a whole. Therefore, the quality of education reflects the quality of people that are the product of educational management in the context of Thai society. However, in the current situation, most educational institutions do not equality in terms of budget, personnel quality, or even learners’ factors including other encouraging factors such as the cooperation of the school board, Supporting from local government organizations. These things affect the quality of education. The National Education Act 1999 and the amendment (No 2) B.E. 2002, therefore, the agency and the educational institution shall have an internal quality assurance system of the school which leads to the establishment of educational standards.